TEACHING STUDENTS TO WTHE USE OF MICROCOMPUTER IN TEACHING STUDENTS - Nugmanova, С.А.; Erbolat, М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article discusses the prerequisites for using the Arduino Uno brand of hardware and software, which are necessary when creating simple automation and robotics systems for non-professional users in teaching the basics of microcontroller robotics. The article discusses the capabilities of the Arduino hardware computing platform as applied to mechatronic complexes. A functional description and technical specifications are given using the Arduino UNO board as an example. A comparative analysis of the hardware of the most relevant boards has been compiled. The prospects for the use of the Arduino microprocessor platform for training and design in the field of physical process control are determined. The article compares various microcontrollers Arduino, Raspberry Pi, Lego Mindstroms. based on the analysis, it is concluded that Lego Mindstroms microcontrollers are the most convenient for teaching younger students, and for teaching middle and high school students - Arduino microcontrollers. Mindstorms microcontrollers are sold complete with instructions, peripherals, parts, and sensors. Their body protects against damage, and familiar to many children LEGO allows you to create various mechanisms and robots using a visual programming language. This set is easily mastered by primary and secondary school students. High school students can develop programming skills in the integrated Arduino environment.